Resistance of Salmonella typhimurium Mutants to Galactose Death - Shuster, C. W. (1969)
A class of galactose-resistant mutants has been derived from strains of Salmonella typhimurium which are defective in uridine diphosphoglucose-4-epimerase. Resistant strains are phenotypically similar to parent organisms but do not lyse in the presence of galactose. Low levels of functional epimerase can be detected in induced cells grown at 20 C but not at 37 C, and acid is not produced from galactose. Sufficient galactose is synthesized at reduced temperatures to fabricate smooth lipopolysaccharide and acceptor sites for phage P22 from galactose-deficient media. The leaky nature of these mutants may account for resistance to galactose death by maintaining galactose metabolites at a subcritical level. Glucose protects sensitive strains by control of levels of toxic metabolites by catabolite repression.